Salinity variability and its correlation with IOD and MJO in the Bali Strait: A depth-resolved FFT analysis - Annastasya Mulia Paradigma; Asri Sawiji; M. Yunan Fahmi (Journal of Marine Resources and Coastal Management, 2025)
The Bali Strait connects the Java Sea in the north to the Indian Ocean in the south, and the interaction between these two regions influences the strait’s oceanographic dynamics, including salinity variability. Large-scale climate phenomena such as the Indian Ocean Dipole (IOD) and the Madden–Julian Oscillation (MJO) play important roles in modulating salinity in these waters. This study aims to analyze the correlation between salinity and both the IOD and MJO in the northern and southern parts of the Bali Strait, using data from 1999 to 2023. Descriptive statistical methods and Fast Fourier Transform (FFT) analyses were employed. The results show that in the northern waters, the direct correlation between salinity and the IOD is generally weak, with the highest value of 0.22794 at a depth of 1.54 m. Correlations with the MJO are also weak and predominantly negative. In contrast, the southern waters exhibit stronger correlations, particularly between salinity and the IOD, with the highest correlation of 0.29537 at a depth of 25.21 m. FFT analysis further supports these findings, indicating that the IOD exerts a more dominant influence on salinity variability than the MJO, especially at shallow depths. Overall, the IOD has a more significant and consistent impact on salinity variability in the Bali Strait, particularly in the southern region, while the influence of the MJO remains relatively weak.